Translation and validation of the Indonesian version of the Family Support Scale (FSS) for elderly - Kurniawan, Didi; Sahar, Junaiti; Rekawati, Etty; Sartika, Ratu Ayu Dewi (Lentera Perawat, 2025)
Abstract Background: Family support is a crucial determinant of elderly wellbeing, influencing emotional stability, independence, and overall quality of life. The Family Support Scale (FSS) is widely used internationally to measure perceived family support; however, no standardized Indonesian version has been available for elderly populations. Objective: This study aimed to translate, culturally adapt, and evaluate the validity and reliability of the Family Support Scale (FSS) for Older People into the Indonesian language for use among the elderly. Methods: A methodological design was applied using a standardized back-translation procedure encompassing forward translation, synthesis, blind back-translation, and expert harmonization. Fifty elderly respondents aged ≥60 years in Pekanbaru were recruited to assess the instrument’s psychometric properties. Construct validity was evaluated through corrected item–total correlation, while reliability was measured using Cronbach’s Alpha. Results: All 20 items demonstrated acceptable corrected item–total correlation values (>0.30), indicating good construct validity. Reliability testing yielded a Cronbach’s Alpha of 0.949, reflecting excellent internal consistency. The translation and cultural adaptation process successfully preserved semantic, cultural, and conceptual equivalence with the original instrument. Conclusion: The Indonesian version of the FSS is valid and reliable for assessing perceived family support among the elderly in Indonesia. The instrument is suitable for use in clinical practice, community health assessments, and elderly-focused research. Future studies should include larger and more diverse samples and incorporate exploratory and confirmatory factor analyses to further strengthen the construct structure.